Aspekt chirurgiczny opieki nad pacjentem z dysplazją obojczykowo-czaszkową - opis przypadku = Surgical aspect of patient care with cleidocranial dysplasia - case report - Aleksandra Szczepkowska; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2016)
Szczepkowska Aleksandra, Osica Piotr, Janas-Naze Anna. Aspekt chirurgiczny opieki nad pacjentem z dysplazją obojczykowo-czaszkową - opis przypadku = Surgical aspect of patient care with cleidocranial dysplasia - case report. Journal of Education, Health and Sport. 2016;6(4):355-363. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50488 http://ojs.ukw.edu.pl/index.php/johs/article/view/3485     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.04.2016. Revised 25.04.2016. Accepted: 25.04.2016.     Aspekt chirurgiczny opieki nad pacjentem z dysplazją obojczykowo-czaszkową - opis przypadku   Surgical aspect of patient care with cleidocranial dysplasia - case report   Aleksandra Szczepkowska, Piotr Osica, Anna Janas-Naze   Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze   Adres do korespondencji: Aleksandra Szczepkowska Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: aleksandra.szczepkowska@gmail.com tel. 42 675 75 71   Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001   Streszczenie   W pracy przedstawiono przypadek pierwszego etapu leczenia ortodontyczno-chirurgicznego 16-letniej pacjentki z dysplazją obojczykowo-czaszkową, przeprowadzonego w znieczuleniu ogólnym.   Słowa kluczowe: dysplazja obojczykowo-czaszkowa, chirurgia, znieczulenie ogólne.   Abstract   The work shows a case of the first stage of orthodontic-surgical treatment 16-year-old patient suffering with cleidocranial dysplasia, which was carried out under general anesthesia.   Keywords: cleidocranial dysostosis, surgery, general anesthesia.